2011
DOI: 10.1038/ng.948
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for compensatory upregulation of expressed X-linked genes in mammals, Caenorhabditis elegans and Drosophila melanogaster

Abstract: Many animal species use a chromosome-based mechanism of sex determination, which has led to the coordinate evolution of dosage-compensation systems. Dosage compensation not only corrects the imbalance in the number of X chromosomes between the sexes but also is hypothesized to correct dosage imbalance within cells that is due to monoallelic X-linked expression and biallelic autosomal expression, by upregulating X-linked genes twofold (termed ‘Ohno’s hypothesis’). Although this hypothesis is well supported by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
359
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(393 citation statements)
references
References 62 publications
25
359
3
1
Order By: Relevance
“…To equalize the expression of the X chromosome between hermaphrodites (which have two X chromosomes) and males (which have only a single X chromosome), the expression of genes on the X chromosomes in hermaphrodites is reduced by twofold in a process known as dosage compensation (for review, see Meyer 2010). This is in contrast to dosage compensation in mammals where in cells carrying two X chromosomes, one of the X chromosomes is inactivated while dosage-sensitive genes in the other are upregulated (Deng et al 2011). A key component of the dosage-compensation machinery in C. elegans is the dosage compensation complex (DCC), which is structurally similar to the condensin complex that can induce structural changes to DNA (Sharma et al 2014;Lau and Csankovszki 2015).…”
Section: Features Of C Elegans Chromosome Organizationmentioning
confidence: 57%
“…To equalize the expression of the X chromosome between hermaphrodites (which have two X chromosomes) and males (which have only a single X chromosome), the expression of genes on the X chromosomes in hermaphrodites is reduced by twofold in a process known as dosage compensation (for review, see Meyer 2010). This is in contrast to dosage compensation in mammals where in cells carrying two X chromosomes, one of the X chromosomes is inactivated while dosage-sensitive genes in the other are upregulated (Deng et al 2011). A key component of the dosage-compensation machinery in C. elegans is the dosage compensation complex (DCC), which is structurally similar to the condensin complex that can induce structural changes to DNA (Sharma et al 2014;Lau and Csankovszki 2015).…”
Section: Features Of C Elegans Chromosome Organizationmentioning
confidence: 57%
“…The association of methylation with gene expression is also suggested by the observation that the X chromosome is more heavily methylated than all other chromosomes. In Drosophila, the X chromosome is subject to gene dosage compensation through the up-regulation of X-linked genes in males (Baker et al 1994;Deng et al 2011). Although it is tempting to speculate that the higher density of methylation on the X chromosome is involved in dosage compensation, it is not clear how methylation would contribute to the process.…”
Section: Discussionmentioning
confidence: 99%
“…However, RNA sequencing (RNA-Seq) revealed an X:AA expression ratio of ∼0.5, refuting Ohno's hypothesis (12). A number of authors subsequently noted that the fraction of inactive genes is greater in X than in autosomes and that X:AA ∼1 when only active genes are considered (14)(15)(16)(17). We suggested that the extra inactive genes in X originated from the most weakly expressed genes in X as a consequence of Y degeneration, and that X:AA ∼0.5 when appropriate sets of active genes are compared (13).…”
mentioning
confidence: 92%